EXPLORING THE RELATIONSHIP BETWEEN ARTIFICIAL INTELLIGENCE (AI) ADOPTION IN HUMAN RESOURCE (HR) AND ORGANIZATIONAL PRODUCTIVITY - Beenish Ahmed; Shahrukh Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
The ultimate aim of this research study is to substantiate the relationship between Artificial Intelligence (AI) implementation in Human Resources(HR) and organizational performance. AI technologies, including machine learning (ML), natural language processing (NLP) and Robotic Process Automation (RPA), are on the brink of transforming HR activities by automating repetitive tasks, enhancing decision-making skills and driving employee engagement. Utilising a mixed research methodology, the study involves literature review and case studies/ experiments along with surveys to assess how AI could potentially influence HR cost efficiency by streamlining decision-making or workforce planning. The answer: the seemingly trivial process efficiencies and quality of decision-making that lead to productivity improvements through AI adoption. Despite that, the paper highlights a number of issues which could arise such as data protection and possible ethical concerns as well creating HR professionals better equipped to understand it. The study closes with recommendations for better use of AI by HR and notes that the presented solutions are a necessary condition to harness benefits from AI.